Management Regimes established for REDD+ and their Adaptability to the Institutional and Ecological Conditions: A case of Ongo Community Forest, Masindi District, Uganda. - Nabanoga, G.; Namaalwa, J.; Ssenyonjo, E.; Nantongo, M. (Noragric Report, 2015)
This report is one of the outputs of the project “Man and forests – an evaluation of management strategies for reduced deforestation” which aimed at evaluating the different management strategies undertaken to obtain reduced deforestation in tropical forests and hence maintain the various ecosystem services delivered. One component of this project focused on characterizing the management regimes established in the REDD+ pilot area and how well the REDD+ regime is adapted to the local institutional and ecological conditions. The site under investigation is a communally owned forest known as Ongo community forest, where the Environmental Conservation Trust of Uganda (ECOTRUST), is piloting REDD+ activities. The investigations entailed discussions with the implementing agent the ECOTRUST, local council leaders, forest management committee members, Masindi district technical staff and the local community members.